Peer-Review Article Effects of Management Development Training for Public Senior High Schools Heads on Teachers’ Performance in Ghana: Effects of Management Development Training for Public Senior High Schools Heads on Teachers’ Performance in Central Region, Ghana - Francis Kwesi Nsakwa Gabriel-Wettey; Meier Corinne (Universitas Ahmad Dahlan, 2023)
Management Development Training (MDT) is central to every organisation helping to attain institutional goals; improve effectiveness and efficiency; and creates a dynamic entity. The purpose of this study was to investigate the effects of MDT for public senior high schools (SHS) heads on teachers’ performance in the Central Region of Ghana. A mixed methods approach (MMA) based on explanatory sequential mixed methods design was adopted. Primary data were collected through structured questionnaire distributed to 280 public SHS teachers using a simple random sampling technique. In addition, semi-structured interview schedule was used to gather primary data from seven school heads and three district training officers (DTOs) using purposive and census sampling techniques respectively. Document analysis was employed to access relevant secondary data. While-SPSS (24.0) was used in the data analysis process. The findings indicated that MDT programmes led to improved competence in school heads, while teachers developed effective classroom management skills and reported performance. The recommendation is that Ghana’s government, through the Ministry of Education (MoE)/Ghana Education Service (GES), establishes a special MDT institution- to focus solely on developing managerial and leadership skills in school heads, as well as assistant, newly appointed and “would-be” heads. The MoE/GES should develop a comprehensive MDT policy which makes it compulsory for all new and practising school heads to undergo such training before and after assuming office. The study concluded that MDT for school heads have positive effects on both heads and teachers’ performances.